Efetividade da escada para peixes da UHE Engenheiro Sergio Motta - CESP para espécies de peixes migradoras neotropicais - Wagner, Ricardo Luiz (2010)
Transposition systems for fishes at the dam hydroelectric power plants are designed to mitigate impacts, however, it is necessary for these systems to be evaluated and monitored. This study, conducted at the fish ladder of the Engenheiro Sergio Motta Hydroelectric Power Plant - CESP, during the period from November 2009 to April 2010, aimed to analyze the effectiveness of this system, considering two aspects needed for analysis: the rate of attractiveness, and subsequently, the efficiency of the fish ladder. The rate of attractiveness considered the percentage of individuals who found the entry, while the efficiency was calculated from the percentage ascending along the fish ladder through the Ascend Function. The Risk Function was used to identify sites that might hinder the ascent of the species studied. The RFID (Radio Frequency Identification) system was utilized in the study, with the installation of eight antennae along the fish ladder and transponders (PIT tags) of 32mm were implanted in four long-distance migratory fish species. We considered two sites for the release after the tagging: in the first, designated as the ramp, situated approximately 1,100m downstream the entrance to the fish ladder, 757 individuals were tagged, of which 151 were Brycon orbignyanus, 204 Piaractus mesopotamicus, 196 Prochilodus lineatus and 206 Rhinelepis aspera. At the second site, the pool 11 of the ladder, 317 individuals were tagged distributed in 100 P. mesopotamicus, 109 P. lineatus and 108 R. aspera. The results of the attractiveness for individuals released in the ramp were 15.89% for B. orbignyanus, 55.39% for P. mesopotamicus, 7.4% for P. lineatus and 24.73% for R. aspera. The results of the estimates of efficiency whith the use of the Ascend Function were differentiated for part of the species studied. For B. orbignyanus released in the ramp efficiency was 79%. P. mesopotamicus obtained 94% when released in the ramp, and 78% for the fishes released in the pool 11. The results for P. lineatus was 100% for the fishes released in the ramp and 69% for the pool 11. For the R. aspera percentages of 43 and 31% were observed in the ramp and in pool 11, respectively. Significant differences were verified between species regarding the time of arrival at the fish ladder: R. aspera (lowest time) differed from all the species and B. orbignyanus differed from P. mesopotamicus. The times spent traveling along the fish ladder were different for P. mesopotamicus and P. lineatus, with greater time accumulated by R. aspera. In the risk estimates, the highest values occurred in the initial portion, i.e., up the third antenna, suggesting that some hydrological variable may exist in this segment imposing greater restrictions upon the species studied. The assessments and monitoring of the effectiveness of the fish ladder in the Engenheiro Sergio Motta Hydroelectric Power Plant, for the species studied, as well as other target species, should be continued over the long term, in order to verify if this passage permits the fishes, within the reproductive period (piracema) to find and overcome the passage in good time to undertake their reproduction in the tributaries situated upstream of the dam.